2016
DOI: 10.1021/acs.langmuir.6b02590
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Stimuli-Responsive W/O/W Multiple Emulsions Prepared by One-Step Mixing with a Single Diblock Copolymer Emulsifier

Abstract: Multiple water-in-oil-in-water (W/O/W) emulsions are promising materials to design carriers of hydrophilic molecules or drug delivery systems, provided stability issues are solved and biocompatible chemicals can be used. In this work, we designed a biocompatible amphiphilic copolymer poly (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Evidently, the inherent amphiphilic nature and high interfacial activity of these PZs facilitates the formation of complex emulsions by simple vortex mixing, as opposed to multistep and/or microfluidic techniques. [28][29][30] In addition to using a single polymeric surfactant to stabilize these types of droplets, our system employs homopolymers, rather than block or other architectural variations, thus offering a simplified synthetic approach. [28,[31][32][33][34] The oil droplets containing smaller water droplets ranged primarily from ≈10 to ≈50 μm diameter, while smaller droplets were also observed.…”
Section: Using Ammonium Sulfonate Pzs In Complex Emulsion Formationmentioning
confidence: 99%
“…Evidently, the inherent amphiphilic nature and high interfacial activity of these PZs facilitates the formation of complex emulsions by simple vortex mixing, as opposed to multistep and/or microfluidic techniques. [28][29][30] In addition to using a single polymeric surfactant to stabilize these types of droplets, our system employs homopolymers, rather than block or other architectural variations, thus offering a simplified synthetic approach. [28,[31][32][33][34] The oil droplets containing smaller water droplets ranged primarily from ≈10 to ≈50 μm diameter, while smaller droplets were also observed.…”
Section: Using Ammonium Sulfonate Pzs In Complex Emulsion Formationmentioning
confidence: 99%
“…Moreover, Wang et al reported the morphologies transition induced by varying the amphiphilicity of BCP based on supramolecules or pH-sensitive BCP, and multiple 3D macroporous architectures were generated. Guenoun and co-workers demonstrated that emulsions can be stabilized with a single BCP surfactant which was pH- and temperature-responsive. , By varying the pH value and temperature, type of the emulsion was changed from oil-in-water to water-in-oil. More importantly, multiple emulsions could be obtained in this inversion process.…”
Section: Introductionmentioning
confidence: 99%
“…Guenoun and co-workers demonstrated that emulsions can be stabilized with a single BCP surfactant which was pH-and temperature-responsive. 42,43 By varying the pH value and temperature, type of the emulsion was changed from oil-in-water to water-in-oil. More importantly, multiple emulsions could be obtained in this inversion process.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Via multivalent anchoring on the oil/water interphase, these amphiphilic polymers allowed for the long-term stability of the multiple emulsions. [21] Under high pH and ion concentration, the hydrophobicity of the copolymer was increased, and thus triggered phase inversion to form W/O/W double emulsions. [20] In this case, diblock-copolymer-stabilized emulsions were fabricated via single step.…”
Section: Phase Inversion For Multiple Emulsionsmentioning
confidence: 99%